Model Civic Action Pemuda untuk Memberdayakan Disabilitas Berbasis Citienship Education - Saepudin, Epin; Nanggala, Agil (Universitas Negeri Malang, 2025)
The purpose of this study is to analyze the role of youth civic action in overcoming the charity model of disability and the medical or individual model of disability, as well as the model of youth civic action in empowering persons with disabilities. This study used a qualitative descriptive method with observation, interviews, and document study techniques. The results show that youth civic action plays an important role in overcoming the stigma of the charity model of disability and the medical or individual model of disability. Youth civic action is guided by the principles of the social model of disability, which views persons with disabilities as capable of empowerment when supported by inclusive factors. Youth civic action models to empower people with disabilities can be implemented in three ways, by joining formal organizations, volunteering with community groups that support people with disabilities, and participating in collective incidental activities.